Research on concentrated photovoltaic thermal and daylighting (CPVTD) systems using round and flat optical fibers / Afshin Aslian - Afshin , Aslian (2021)
Concentrated photovoltaic and thermal (CPVT) system is proposed. The system concentrates the sunlight and implements solar cells in focal point of a concentrator. Heat collector is located behind the cells and transmits the heat to a heat exchanger. The system has high efficiency in direct sunlight. So, a sun tracker is required as a subsystem. By integrating the function of daylighting to the CPVT system, the functionality of system improves, and the developed system can be deployed in residential buildings. In this research substance-field (Su-Field) and functional analysis of Teoriya Resheniya Izobretatelskikh Zadach (TRIZ) are applied to develop a comprehensive model of problem in integrating three functions i.e. electricity, heat and light into a developed system. The model of concentrated photovoltaic-thermal and daylighting (CPVTD) solar energy system for residential buildings is presented through integrating light function to a CPVT system. Developing a CPVTD system for residential building is a fine process that requires satisfying several design considerations such as total efficiency, thermal, electrical and daylighting performance with significant innovations and improvements. Since a CPVTD is a complex system that consists of combination of different components, the design considerations are interconnected and often conflicting. As a result, multi-variable optimization is often required for increasing the total efficiency, reducing bulk of system, improving reliability and durability and minimizing the total cost. In this research we focused on optical components and heat sink of a CPVTD system. These components are imaging dish, secondary concentrator, optical fiber and heat sink. These components are the main components that convert sunlight to electricity, hot water and daylight. A novel secondary concentrator, a new rectangular optical fiber, and a compact energy conversion device “that we name hear” a receiver is designed and fabricated. In a compact energy conversion device, we can split the bulk of transmitted light for different purposes, i.e. electrical power conversion, heat and daylighting. A glass rectangular optical fiber designed for transmitting sunlight. The fiber simulated, fabricated and tested as a medium for transmitting sunlight from focal point to photovoltaic cells in the compact energy conversion device. A receiver of CPVTD with round optical fiber is fabricated and tested. The results show that using optical fiber as a medium in receiver reduced the temperature of multi-junction cells and increased the distance between the cells. Therefore, the surface of heatsink increased, and heat exchange between fluid and heat sink enhanced.